2019
DOI: 10.32383/appdr/112406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, and Evaluation of Coumarin Hybrids as Antimycobacterial Agents

Abstract: A series of twelve hybrid coumarin analogs were synthesized and screened through HTS for their antimycobacterial activity against Mtb H37Rv. The hybrid molecules were efficiently synthesized by the reactions of 3-(bromoacetyl)coumarin with Biginelli products 2-mercapto-6-oxo-4-aryl-1,6-dihydropyrimidine-5carbonitriles. Of the resulting twelve hybrids, the two compounds 7-(2,4-dichlorophenyl)-5-oxo-3-(2-oxo-2Hchromen-3-yl)-5H-thiazolo[3,2-a] pyrimidine-6-carbonitrile (3d) and 7-(4-nitrophenyl)-5-oxo-3-(2-oxo-2H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The starting blocking unit 2-thiouracil derivative (1) was prepared [31,34] from the classic Biginelli condensation of ethyl cyanoacetate, 2,4dichlorobenzaldehyde and thiourea in basic medium of anhydrous K2CO3.The IR-spectrum of this compound showed absorption at (2227 cm -1 and 1662 cm -1 ) for C≡N and C=O respectively. 1 HNMR spectrum showed a singlet signal at δ 9.70 and δ 11.30 for 2 hydrogens of pyrimidine ring (2NH).…”
Section: Resultsmentioning
confidence: 99%
“…The starting blocking unit 2-thiouracil derivative (1) was prepared [31,34] from the classic Biginelli condensation of ethyl cyanoacetate, 2,4dichlorobenzaldehyde and thiourea in basic medium of anhydrous K2CO3.The IR-spectrum of this compound showed absorption at (2227 cm -1 and 1662 cm -1 ) for C≡N and C=O respectively. 1 HNMR spectrum showed a singlet signal at δ 9.70 and δ 11.30 for 2 hydrogens of pyrimidine ring (2NH).…”
Section: Resultsmentioning
confidence: 99%
“…These products form Scheme 16. Mechanism for the 2H-chromen-thiazol-pyrazol-2H-chromen-2one synthesis (68). [81] (The mechanism was redrawn from literature.)…”
Section: Chemistryselectmentioning
confidence: 99%
“…[80] The reaction of 3-bromoacetylcoumarin (2), 3-(acetoacetyl)coumarin derivatives (67) and thiosemicarbazide (58) under reflux conditions in ethanol was identified as a onepot, multicomponent reaction for the synthesis of 2H-chromenthiazol-pyrazol-2H-chromen-2-one (68) in good yields (Scheme 15). [81] Scheme 16 shows a proposed mechanism [81] pathway for final product production (68). First, the thiosemicarbazide (58) reacts with 3-bromoacetylcoumarin (2), releasing HBr in the process.…”
Section: Chemistryselectmentioning
confidence: 99%
“…
Recently, a molecular hybridization method offered a promising strategy to design new potent hybrid molecules with multi-targeting synergistic effects. 12 Previous studies showed that molecular hybrids containing pyrazole and azo (-N=N-)/hydrazo (=N-NH-) pharmacophores in a single molecular framework resulted in improved antimicrobial potentials. 13,14 In continuation of our endeavors to develop potent and effective antimicrobial agents, 15 this study deals with the optimization of pyrazole-azo/hydrazo molecular hybrid leads as potential antimicrobial agents.
Results and discussion
ChemistrySo far, the majority of previously reported syntheses of arylhydrazono pyrazoles (AHPs) and aryldiazenyl pyrazoles
…”
mentioning
confidence: 99%